COMMUNITY PARTICIPATION IN INSURANCE OWNERSHIP SOCIAL HEALTH TO UNIVERSAL HEALTH COVERAGE (UHC) IN JAMBI CITY - Dwi Noerjoedianto; Andi Subandi; Andy Amir (Pusat Riset dan Inovasi Nasional, 2022)
Introduction: Universal Health Coverage (UHC) is a health financing system that ensures every individual has equitable access, quality and financially affordable health services. BPJS as the organizing body has made efforts to encourage the achievement of UHC but in it’s implementation there are many obstacles.Method: This research is an analytical qualitative research. Result: Public knowledge about health insurance is still low, the availability of health facilities and coverage of health services are in accordance with standards.Discussion: There are still many people who do not know the importance of being a participant in health insurance.